Sistem Pengendalian Internal, Kepuasan Kerja dan Kecenderungan Kecurangan Akuntansi : Survey pada Bank Sulselbar Cabang Sinjai - Fatahuddin, Ahmad; Liline, Ledy Jeane (Insan Cita Bongaya Research Journal, 2025)
Accounting fraud has received a lot of public attention as a dynamic that is the center of attention for business people. This study aims to test and analyze the influence of internal control systems and job satisfaction on the tendency of accounting fraud. The research was conducted on employees of Bank Sulsebar Sinjai Branch. Data collection used a questionnaire technique and the number that could be collected and analyzed as many as 45 questionnaires from 45 respondents/employees who filled out the questionnaire. To conduct data analysis, multiple regression analysis was used using the SPSS application to process data. The results of the study show that the internal control system has a negative effect on the tendency of accounting fraud. Job satisfaction has a negative effect on the tendency of accounting fraud